Feminidad, deseo y utopía: las mujeres de Nosotros - García Sala, Iván (Eslavística Complutense, 2007)
This article is focused on the analysis of the role played by desire and femininity represented by two protagonists in the anti-utopian system showed in the novel We by Zamiatin. The two characters are analysed as images of femininity confronted with the masculinity of utopian thinking.